2010
DOI: 10.1002/ajim.20791
|View full text |Cite
|
Sign up to set email alerts
|

Using community‐based participatory research to design and initiate a study on immigrant worker health and safety in San Francisco's Chinatown restaurants

Abstract: CBPR holds promise for both studying worker health and safety among immigrant Chinese restaurant workers and developing culturally appropriate research tools. A new observational checklist also has potential for restaurant-level data collection on worker health and safety conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
0
1

Year Published

2011
2011
2015
2015

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 121 publications
(34 citation statements)
references
References 24 publications
0
32
0
1
Order By: Relevance
“…Although a detailed presentation of the study findings is beyond the scope of this paper and is available elsewhere, 3,14,[25][26][27] we highlight here those of most relevance to workers, particularly in relation to their primary concerns, wage theft, and other basic worker rights violations. Survey results (n0405) indicated that almost 60 % of participants had experienced wage theft in at least one of its forms.…”
Section: Study Findingsmentioning
confidence: 99%
See 2 more Smart Citations
“…Although a detailed presentation of the study findings is beyond the scope of this paper and is available elsewhere, 3,14,[25][26][27] we highlight here those of most relevance to workers, particularly in relation to their primary concerns, wage theft, and other basic worker rights violations. Survey results (n0405) indicated that almost 60 % of participants had experienced wage theft in at least one of its forms.…”
Section: Study Findingsmentioning
confidence: 99%
“…These experiences contributed to the health department's examination of internal practices and the subsequent exploration of withholding health permits to restaurants found to be in violation of minimum wage laws and requiring verification of workers' compensation insurance when issuing business operating licenses. 29 University partners led other publication efforts, 14,25,27,30 and all partners presented on the project at local, national, and international professional and community meetings. It was, however, the community partners-CPA and the worker partners-who led the dissemination of survey and other study findings to the wider community and public and used the findings in support of the central action component of the study.…”
Section: Dissemination and Use Of Findings For Actionmentioning
confidence: 99%
See 1 more Smart Citation
“…28 An orientation to research, rather than a research method, CBPR is "systematic investigation, with the collaboration of those affected by the issue, for the purposes of education and action or effecting change." 29(p2) The topic of wage theft quickly emerged from worker and community partners as the single most important issue on which they wanted to collect data.…”
Section: A Case Study Of Immigrant Restaurant Workers In San Franciscmentioning
confidence: 99%
“…The research aims of this project were to (1) assess labor law compliance and workplace hazards in restaurants in one San Francisco, California, neighborhood; (2) assess the feasibility of using an observational checklist to routinely monitor workplace conditions in the course of regulatory inspections; and (3) assess the relationship between observed workplace hazards and food safety scores. Consistent with community-based participatory research (CBPR) principles of generating collective understanding and action to address a priority social problem, [18][19][20] this article describes the process of creating and applying the checklist and the findings from this application. We discuss lessons learned regarding the utility of the checklist as a data-collection instrument and the feasibility of incorporating the checklist into routine environmental inspections.…”
mentioning
confidence: 99%